Strategi Pemberdayaan UMKM Kabupaten Cirebon dalam Mendukung Pencapaian Sustainable Development Goals (SDGs) Berbasis Maqashid Al-Shari’ah - Alvi Fauziyah; Azriel Khoerul Ihsan; Junemi Junemi; Nurul Hasanah; Gama Pratama; Mohammad Ridwan (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
. This study aims to provide an in-depth examination of empowerment strategies for micro, small, and medium enterprises (MSMEs) in Cirebon Regency to support the achievement of the Sustainable Development Goals (SDGs) through the lens of Maqashid al-Shariah. As a major pillar of the local economy, MSMEs continue to face multiple constraints, including limited financing, inadequate market access, and low levels of Islamic financial literacy. Using a qualitative approach, this study draws upon a wide range of academic literature related to MSME empowerment, the SDGs framework, and Maqashid al-Shariah. The findings indicate that effective MSME empowerment should focus on enhancing business capacity, strengthening literacy and access to sharia-based financial services, and improving the availability of supporting infrastructure. The integration of Maqashid al-Shariah offers a normative foundation for development that not only prioritizes economic advancement but also safeguards essential aspects of life, including wealth, intellect, life, lineage, and faith. The study also identifies several implementation challenges, such as unclear regulatory frameworks, limited public understanding, and the insufficient outreach of Islamic financial services, including the relatively slow development of the halal industry. Overall, comprehensive empowerment strategies grounded in sharia principles are viewed as vital to accelerating the attainment of SDGs across economic, social, and environmental dimensions.